Financial Access and Stability : A Road Map for the Middle East and North Africa - Rocha, Roberto (World Bank, Washington, DC, 2012)
The full report on which this Quick Note is based argues that Middle East and North Africa's (MENA's) financial systems contributed significantly to these unsatisfactory outcomes by failing to provide affordable access to finance to large segments of the enterprise and household sectors. The financial sector is part of the problem and therefore needs to be part of the solution. Any effort to develop a new growth agenda for the region will need to include a significant component of financial sector reforms. This Quick Note is based on the finance flagship report with the same title which provides a diagnostic of financial development in the MENA region and proposes a roadmap for expanding access to finance while preserving financial stability.